Effect of different selection criteria on performance, carcass and meat quality of nellore young bulls - Silva, Juliana; Cônsolo, Nara Regina Brandão; Buarque, Vicente Luiz Macedo; Beline, Mariane; da Silva Martins, Taiane; Lobo, Annelise Aila Gomes; Gómez, Juan Fernando Morales; Eler, Joanir Pereira; Leme, Paulo Roberto; Netto, Arlindo Saran; Gerrard, David Edwin; Baldi, Fernando [UNESP]; et al. (MDPI, 2021)
This study was carried out to evaluate the effects of selection criteria for post-weaning daily gain (PWDG) and early sexual heifer precocity (PP14) on the performance, carcass traits and meat quality of Nellore bulls. In year one, 50 animals were selected according to their expected progeny differences (EPDs) for PWDG and grouped as high (HG) or low (LG) groups. In year two, 50 animals were selected according to EPD for PP14 and also grouped as high (HP) or low (LP). After slaughter, samples of the longissimus muscle area (LMA) were used to evaluate meat quality. Most of performance traits were not affected by the selection criteria. However, the HG group had higher dressing percentage (ρ = 0.028), LMA (ρ = 0.02) and fat trim in the forequarter (ρ = 0.04) compared to the LG group. The HP group tended to have greater dry matter intake (ρ = 0.08), LMA (ρ = 0.05), rump fat (ρ = 0.04), heavier striploins (ρ = 0.07), tenderloins (ρ = 0.09) and briskets (ρ = 0.08) compared with LP group. In conclusion, the selection based on divergent groups PWDG or PP14 has a small impact on performance, carcass and meat quality traits.
Keywords: Bos indicus; Selection criteria; Tenderness; Weight gain; Wholesale cuts